THE USE OF SNAKES AND LADDERS MATH TO THE DEVELOPMENT OF MULTIPLE INTELLEGENCES IN ELEMENTARY SCHOOL MATHEMATICS SUMMATION MATERIALS - Maya Siti Sakdah; Maimunah Maimunah; Maulidya Safaruddin (Universitas Pendidikan Indonesia, 2022)
Each student has a different level of intelligence, as a result their learning needs are also not aligned. Children have multiple intelligences so a strategy is needed to accommodate the intelligence possessed by children. This research was conducted at SD Islam Tepadu Permata Cendekia, Simalungun Regency, to be precise in third grade students. The aim is to see the effectiveness of the Multiple Intelligences Learning Strategy with the help of Snakes and Ladders Math media on addition material in Mathematics. The implementation of this research is in the form of quasi-experimental research with One group pretest posttest design. Data collection is done by applying tests as well as observations. The results of the study showed that there was an increase in the average score of students before and after being given treatment, namely (40 91). So that it can improve children's mathematical logical intelligence and verbal intelligence through tests. In addition, the physical and interpersonal intelligence of students is also seen when the traditional game media is applied. So it can be concluded that the application of Media Snakes and Ladders is effective in developing Multiple Intelligences in class III SDIT Permata Cendekia, Simalungun Regency.